Protein Kinase D Regulates Cell Death Pathways in Experimental Pancreatitis - Yuan, Jingzhen; Liu, Yannan; Tan, Tanya; Guha, Sushovan; Gukovsky, Ilya; Gukovskaya, Anna; Pandol, Stephen J. (Frontiers in Physiology, 2012)
Inflammation and acinar cell necrosis are two major pathological responses of acute pancreatitis, a serious disorder with no current therapies directed to its molecular pathogenesis. Serine/threonine protein kinase D family, which includes PKD/PKD1, PKD2, and PKD3, has been increasingly implicated in the regulation of multiple physiological and pathophysiological effects. We recently reported that PKD/PKD1, the predominant PKD isoform expressed in rat pancreatic acinar cells, mediates early events of pancreatitis including NF-kappaB activation and inappropriate intracellular digestive enzyme activation. In current studies, we investigated the role and mechanisms of PKD/PKD1 in the regulation of necrosis in pancreatic acinar cells by using two novel small molecule PKD inhibitors CID755673 and CRT0066101 and molecular approaches in in vitro and in vivo experimental models of acute pancreatitis. Our results demonstrated that both CID755673 and CRT0066101 are PKD-specific inhibitors and that PKD/PKD1 inhibition by either the chemical inhibitors or specific PKD/PKD1 siRNAs attenuated necrosis while promoting apoptosis induced by pathological doses of cholecystokinin-octapeptide (CCK) in pancreatic acinar cells. Conversely, upregulation of PKD expression in pancreatic acinar cells increased necrosis and decreased apoptosis. We further showed that PKD/PKD1 regulated several key cell death signals including inhibitors of apoptotic proteins (IAPs), caspases, receptor-interacting protein kinase 1 (RIP1) to promote necrosis. PKD/PKD1 inhibition by CID755673 significantly ameliorated necrosis and severity of pancreatitis in an in vivo experimental model of acute pancreatitis. Thus, our studies indicate that PKD/PKD1 is a key mediator of necrosis in acute pancreatitis and that PKD/PKD1 may represent a potential therapeutic target in acute pancreatitis.